The perfect wife [compact disc, unabridged] : a novel - Delaney, JP (Random House Audio, 2019)
A missing woman receives a second chance at life, thanks to her billionaire husband, but the consequences are deadly. Abbie awakens in a daze with no memory of who she is or how she landed in this unsettling condition. The man by her side claims to be her husband. He's an icon of the tech world, the founder of a lucrative robotics company. He tells Abbie that she is a gifted artist, an avid surfer, a loving mother to their young son, and the perfect wife. He says she had a terrible accident five years ago, and that, through a huge technological breakthrough, she has been brought back from the abyss. She is a miracle of science. But as Abbie pieces together memories of her marriage, she begins questioning her husband's motives, and his version of events. Can she trust him when he says he wants them to be together forever? And what really happened to Abbie half a decade ago?